2013
DOI: 10.3126/jpn.v3i5.7868
|View full text |Cite
|
Sign up to set email alerts
|

Surface epithelial tumors of ovary - an analysis in a tertiary referral hospital

Abstract: Background: Ovarian cancer accounts for 3% of all cancers in females. About 80% of these are benign, and they occur mostly in young women between 20 and 45 years. Borderline tumors occur at slightly older ages while incidence of malignant tumors increases with age, occurring predominantly in perimenopausal and postmenopausal women. About 190,000 new cases and 114,000 deaths from ovarian cancer are estimated to occur annually worldwide. The aim of the study was to fi nd the incidence of surface ovarian tumor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
4
4
0
Order By: Relevance
“…The most common tumors were benign serous tumors accounting for 90 % of the serous surface epithelial tumors and 44.9 % of all surface epithelial tumors, mostly presenting in females of the reproductive age group. However our study is almost consistent with the findings of study done by Ghartimagar et al which showed an incidence of benign serous surface epithelial tumors 49.4 % among of all surface epithelial tumors [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…The most common tumors were benign serous tumors accounting for 90 % of the serous surface epithelial tumors and 44.9 % of all surface epithelial tumors, mostly presenting in females of the reproductive age group. However our study is almost consistent with the findings of study done by Ghartimagar et al which showed an incidence of benign serous surface epithelial tumors 49.4 % among of all surface epithelial tumors [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…[13][14][15] It has been reported previously that benign EOT occur in younger age groups, the borderline tumours in the fourth to fifth decades and malignant in older ages beyond the sixth decade of life. [16 ] The findings from the present study confirmed this tendency and it appears that there is an age proportion for benign, borderline and malignant EOTs all over the world. The benign EOTS affect younger women with many cases diagnosed between the second and the third decades of life; the borderline tumours affect relatively older ages in the sixth decade while malignant cases occur in much older patients in this environment.…”
Section: Discussionsupporting
confidence: 86%
“…Ghartimagar D et al noted age ranging from 13 to 90 years in their study of 310 cases of ovarian tumors. [9] Chhanda Das et al reported 5 to 62 years in their study of 50 cases of ovarian neoplasms which was similar to other studies. [6,10] Most benign tumors occurred in the age range of 21 to 50 years that was consistent with other studies.…”
Section: Discussionsupporting
confidence: 83%